2021
DOI: 10.1177/15353702211037261
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus microRNA BART10-3p promotes dedifferentiation and proliferation of nasopharyngeal carcinoma by targeting ALK7

Abstract: Non-keratinizing nasopharyngeal carcinoma, the major subtype of nasopharyngeal carcinoma, is characterized by low differentiation and a close relation to Epstein-Barr virus infection, which indicates a link between Epstein-Barr virus oncogenesis and loss of differentiation, and raises our interest in investigating the involvement of Epstein-Barr virus in nasopharyngeal carcinoma dedifferentiation. Our previous study showed abundant expression of an Epstein-Barr virus-encoded microRNA, BART10-3p, in nasopharyng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The expression of miR-BARTs 8-3p, 9-5p, 10-3p, and 22 was strongly correlated with an increase in tumor proliferation markers and signatures (Figure 8D). This is supported by experimental studies showing that each of these miRNAs induced proliferation in cell line models [80][81][82][83][84]. Importantly, this high proliferation index is somehow antagonistic to immune infiltration.…”
Section: Discussionmentioning
confidence: 68%
“…The expression of miR-BARTs 8-3p, 9-5p, 10-3p, and 22 was strongly correlated with an increase in tumor proliferation markers and signatures (Figure 8D). This is supported by experimental studies showing that each of these miRNAs induced proliferation in cell line models [80][81][82][83][84]. Importantly, this high proliferation index is somehow antagonistic to immune infiltration.…”
Section: Discussionmentioning
confidence: 68%
“…And Luo etc. demonstrated that differentiation is close to EBV, which indicates that it was a link between EBV and NPC [ 13 ]. Based on clinical consensus and the previous research, we kept the pathological in the model.…”
Section: Resultsmentioning
confidence: 99%